GAMBARAN KADAR HIGH DENSITY LIPOPROTEIN PADA REMAJA OBES DI KABUPATEN MINAHASA - Togelang, Lidya; ., Fatimawali; Manampiring, Aaltje (eBiomedik, 2013)
Abstract: Obesity is the multifactorial disease. Several genetic, behavioral, and physiological factors play a role in etiology of obesity. WHO stated that obesity was global epidemy and become health problem that must be solved. There are correlation of obesity with atherogenic dyslipidemia (elevated of triacylglycerol levels or low levels of HDL cholesterol). HDL cholesterol is the good cholesterol, it removes harmful bad cholesterol from where it doesn't belong. The research was to describe HDL cholesterol levels. A cross sectional study was conducted to obese adolescent in SMK Negeri 2 and 3 Tondano City. The target population of the research was the 1st, 2nd and 3rd grade students. To determine if the students is obese or non-obese, researcher use the method of measuring the waist circumference based on the theory of visceral obesity, then afterwards researcher took a blood sample of the students. In this research, involved 54 obesity students who are willing to partake and the result indicates that 54 obesity students (100%) had low HDL cholesterol levels. It may be caused by several genetic, behavioral, and physiological of the students. It is expected, that the results of this research can be use in developing the prevention and treatments of the low levels of HDL cholesterol in obese adolescent. Keywords: HDL cholesterol, obesity. Abstrak: Obesitas adalah penyakit multifaktorial. Beberapa faktor genetik, kebiasaan, dan aktifitas fisik berperan dalam menyebabkan obesitas. WHO menyatakan bahwa obesitas merupakan epedemik global dan menjadi masalah kesehatan yang harus diselesaikan. Adanya hubungan antara obesitas dengan aterogenik dislipidemia (peningkatan kadar triasilgliserol dan rendahnya kadar kolesterol HDL). Kolesterol HDL adalah kolesterol baik, yang membuang kolesterol jahat yang berbahaya bila tidak digunakan lagi. Penelitian ini bertujuan untuk menggambarkan kadar kolesterol HDL. Studi cross sectional diterapkan pada remaja obes di SMK Negeri 2 dan 3 Kota Tondano. Populasi target dari penelitian ini adalah siswa kelas 1,2, dan 3. Untuk membedakan para siswa obes dan non-obes, peneliti menggunakan metode pengukuran lingkar pinggang yang berdasarkan pada obesitas sentral, setelah itu peneliti mengambil sampel darah dari para siswa. Dalam penelitan, dilibatkan 54 siswa obes yang menyetujui untuk berpatisipasi dan hasilnya didapatkan 54 siswa obes (100%) memiliki kadar kolesterol yang rendah. Ini mungkin disebabkan oleh beberapa faktor genetik, kebiasaan, dan aktifitas fisik para siswa. Diharapkan, dari hasil penelitian dapat digunakan untuk mengembangkan pencegahan dan penatalaksanaan dari rendahnya kadar kolesterol HDL pada remaja obes. Kata Kunci: Kolesterol HDL, obesitas.